In vitro evaluation, molecular docking, and molecular dynamics studies of resorcinol derivatives against yeast α‐glucosidase - Danova, Ade; Hermawati, Elvira; Chavasiri, Warinthorn; Mujahidin, Didin; Musthapa, Iqbal; Kurniadewi, Fera (Indonesian Journal of Biotechnology, 2025)
Nine resorcinol derivatives were evaluated for their ability to inhibit yeast α‐glucosidase using the in vitro method. Three molecular docking programs (Autodock Vina, Autodock4 and DockThor) were employed to determine the binding energies. The results showed that two resorcinol derivatives possessing butanoyl (1) and butyl (9) groups demonstrated good inhibitory activity against α‐glucosidase, with IC50 values of 75.9 and 33.3 µM respectively, compared with other derivatives (2–8) and acarbose (IC50 = 832.8 µM). Furthermore, molecular docking indicated that compounds 1 and 9 had better binding affinities than acarbose and the native ligand. Both compounds showed similar interactions with Asp349 and Glu408, which were associated with acarbose and the native ligand. Moreover, molecular dynamics analysis indicated that compound 9 exhibited greater stability than compound 1 when complexed with α‐glucosidase. Therefore, compound 9 has the potential for further studies, both in vitro and in vivo, to evaluate its toxicity, side effects and efficacy.